The discriminative value of inflammatory back pain in patients with persistent low back pain. (3rd July 2016) - Arnbak, B; Hendricks, O; Hørslev-Petersen, K; Jurik, AG; Pedersen, SJ; Østergaard, M; Hermansen, LT; Loft, AG; Jensen, TS; Manniche, C
Abstract : Objectives : To estimate the prevalence of inflammatory back pain (IBP) characteristics and analyse the discriminative value of IBP relative to axial spondyloarthritis (SpA) according to the Assessment of SpondyloArthritis international Society (ASAS) criteria. Method : Patients who had low back pain for > 3 months were selected from a cohort of secondary care patients aged 18–40 years. Data included information on SpA features, human leucocyte antigen (HLA)-B27 typing, C-reactive protein (CRP) level, magnetic resonance imaging (MRI) of the sacroiliac joints, and self-reported IBP questions covering the pain characteristics included in the Calin, Berlin, and ASAS IBP definitions. Results : Of the 759 included patients, 99% [95% confidence interval (CI) 98–100] had at least one IBP characteristic. The prevalence of the single IBP characteristics ranged from 10% (95% CI 7–12) for 'pain worst in the morning' to 79% (95% CI 76–82) for 'morning stiffness'. Two-thirds of the patients (67%, 95% CI 63–70), met at least one of the three IBP definitions. In all, 86 (11%) were classified as 'SpA according to ASAS'. All three IBP definitions were significantly associated with 'SpA according to ASAS'; however, the discriminative value was low, with sensitivity, specificity, and balanced accuracy values of 64, 50, and 57% for Calin, 59, 60, and 60% for Berlin, and 35, 79, and 57% for ASAS IBP definitions, respectively. Conclusions : In this study population, IBP characteristics were in general common and the discriminative value was low, as IBP could not differentiate patients with SpA according to ASAS criteria from patients with other causes of back pain.